Analysis Of Farmers' Perceptions Of The Need For Agricultural Financing Products At Islamic Banks (Study on The Community of Serba Jadi Subdistrict, East Aceh Regency) - Iskandar, Evy; Ayumiati, Ayumiati; Effendi, Kasri; Jalil, Ivon (JIMEBIS: Scientific Journal of Students Islamic Economics and Business, 2025)
Financing agricultural products in Serba Jadi District is a need for pre- and post-harvest farmers in increasing product excellence. The existence of Islamic banks which are far away and difficult to access has not made a significant contribution in increasing financial inclusion. This study aims to identify the level of farmers' perception of agricultural financing needs. Quantitative approach with associative research type and probability sampling technique with cluster random sampling type of 94 farmers in 18 villages in Serba Jadi District, East Aceh Regency. The results of simple linear regression data analysis prove that the level of farmer perception has no effect on agricultural financing needs.